STRATEGIE KONKURENCJI JUTRA - Cyrson, Edward (Wydział Prawa i Administracji UAM, 2001)
Some rapid and profound changes have been taking place in the contemporary corporate environment. The most powerful of them is a revolution in the economics of information. It acts as a catalyst and accelerator for all other industries. These changes are undermining the foundations of the present analysis of the competitive strategy, its logic and practice. The basic analytical tool of competitive advantage - i.e. the vertically integrated value chain is coming under attack. Its effectiveness had been supported by the information asymmetries that held the value chain’s layers together. Not anymore, though. The rapid development of information technologies enables an open and virtually cost-free exchange of information of all kinds, and it is now melting this asymmetry. Its immediate consequence is an unprecedented separation of popular layers of the vertically integrated value chain into stand-alone, narrowly defined businesses. Therefore, competitive advantage across the entire value change no longer matters, as it is advantage in each layer that counts. As a result, the new unit of strategic analysis is the layer. The above deconstruction of the traditional vertically integrated value chain motivates an emergence of new types of competitive strategies: the orchestration, seizure, creation and integration of the links.
COMPETITIVE STRATEGIES FOR THE FUTURE